Spiritual Well-Being of Cancer Patients Undergoing Chemotherapy in Yogyakarta - Ike Wuri Winahyu Sari; Deby Zulkarnain Rahadian Syah (Universitas STRADA Indonesia, 2024)
Background: In order to provide holistic care and advance spiritual well-being, it is essential to identify and meet the patient's spiritual well-being. Purpose: This study aimed to determine the spiritual well-being of cancer patients undergoing chemotherapy in Yogyakarta. Methods: This study used a cross-sectional approach with a sample of 50 cancer patients undergoing chemotherapy at the One Day Care (ODC) oncology clinic, a private hospital in Yogyakarta, which was taken using a purposive sampling technique. The measurement tool used is the Spiritual Well-Being Scale (SWBS) questionnaire which consists of 20 items. Data analysis in this study used descriptive statistics and cross tabulation to determine the comparison between spiritual well-being of cancer patients undergoing chemotherapy based on their demographic characteristics. Results: Spiritual well-being has a higher score in patients who are female (92.53±10.49), have higher education (92.67±10.84), are widowers/widows (97.00 ± 4.24), receive treatment of the partner (93.81 ± 10.30), and had stage III disease (92.88 ± 9.54). Conclusion: An accurate assessment of spirituality in patients can be a clinical guide in establishing nursing diagnoses of spiritual distress or readiness to improve spiritual well-being.